2021
DOI: 10.1088/1741-4326/ac2ff6
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal modeling of plasma response to RMP fields for HL-2M

Abstract: The plasma response to the n = 1, 2, 4 (n is the toroidal mode number) resonant magnetic perturbation (RMP) fields, and the consequences on the fast ion confinement, are numerically investigated for a reference high-pressure plasma in HL-2M, by utilizing the linear resistive magnetohydrodynamic code MARS-F (Liu et al 2000 Phys. Plasmas 7 3681). The best coil current configurations, in terms of the coil phasing between the upper and lower rows of coils for controlling type-I edge localized modes (ELMs) in HL-2M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…We find that the normal displacement strongly peaks near the X-point, indicating that the RMP field induces a strong edge peeling response. This type of plasma response, associated with the n = 1 RMP in odd parity configuration in HL-2A, has been found to strongly facilitate ELM control in other devices [36][37][38][39] as well as in HL-2A [35].…”
Section: Linear Plasma Responsementioning
confidence: 83%
“…We find that the normal displacement strongly peaks near the X-point, indicating that the RMP field induces a strong edge peeling response. This type of plasma response, associated with the n = 1 RMP in odd parity configuration in HL-2A, has been found to strongly facilitate ELM control in other devices [36][37][38][39] as well as in HL-2A [35].…”
Section: Linear Plasma Responsementioning
confidence: 83%
“…The parallel component of the perturbed velocity is taken along the equilibrium field line. The damping term does not play a significant role at low-beta (as in the work presented here), but it is essential for high-beta plasmas [30,31]. In this work it is fixed to κ ∥ = 1.5 for consistency with previous work on MAST [24].…”
Section: The Mars-f Modelmentioning
confidence: 88%
“…It is demonstrated that the strong SWD plays an important role in high β N (e.g. β N >∼ 0.85β limit N ) plasma [64][65][66]. In this work, since β N = 1.7 is far below the Troyon no-wall beta limit (β limit N 2.9) for the n = 2 external kink instability, the weak SWD with κ = 0.1 is assumed.…”
Section: Modeling Approachmentioning
confidence: 94%